Persepsi pensyarah dan pelajar terhadap "E-Learning system" di Unimas - Bong, Joon Ai (Universiti Malaysia Sarawak, 2003)
The main objective of this study is to determine the lecturers and students' perception towards E-learning System in UNIMAS.